Best Practices to Prevent Complications in Non-Invasive Ventilation - Celina Maria Peixoto Ladeira; Luís Paiva; Hélène Ferreira Malta (CURARE Journal of Nursing)
Objective: Non-invasive ventilation (NIV) refers to the delivery of positive pressure ventilation without using invasive methods. To develop a best practices protocol to standardise nursing interventions for preventing complications associated with the interface and air pressure/flow and to optimise NIV. Methods: A non-probability snowball, convenience or intentional study was carried out using the Delphi technique. Online questionnaires in two rounds were applied to 24 nurses who were experts in the field under study, selected according to previously defined criteria. Results: The expert panel reached a consensus on 67 nursing interventions to prevent two types of NIV complications: those associated with the interface (facial pain or discomfort, noise, skin lesions on the nasal bridge and face, carbon dioxide rebreathing, claustrophobia, and patient-ventilator asynchrony) and those associated with air pressure/flow (air leaks; nasal and oral dryness/congestion, conjunctivitis; aerophagia and abdominal distension). Conclusion: A validated protocol for patients undergoing NIV can support decision-making, provide a set of evidence-based interventions and promote the quality and standardisation of nursing care practices to improve the effectiveness and, consequently, the success of NIV.